2022
DOI: 10.7717/peerj.13332
|View full text |Cite
|
Sign up to set email alerts
|

The effects of music on cardiorespiratory endurance and muscular fitness in recreationally active individuals: a narrative review

Abstract: Music is made up of several features (e.g., melody and rhythm) and it accompanies our life in different daily activities. During the last years, there was a growing interest in research about the music-related effects in the exercise domain. Music stimuli could act as an ergogenic effect leading to improvements in health-related and physical fitness components like cardiorespiratory endurance and muscular fitness. Moreover, listening to music may positively affect individuals’ psychological state which could l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Musical preferences have been recognized as a moderator factor that might influence the relationship between a musical stimulus and the individuals’ responses to it. It has been assessed that familiarity with a melody might positively influence emotional responses, thereby increasing exercise performance ( Karageorghis, 2020 ; Terry et al, 2020 ; Greco et al, 2022 ). However, it is not yet clear whether the main effect on muscle strength is given by the music characteristics ( i.e ., tempo > 120 bpm) or the affective responses consequent to listening to self-selected music.…”
Section: Introductionmentioning
confidence: 99%
“…Musical preferences have been recognized as a moderator factor that might influence the relationship between a musical stimulus and the individuals’ responses to it. It has been assessed that familiarity with a melody might positively influence emotional responses, thereby increasing exercise performance ( Karageorghis, 2020 ; Terry et al, 2020 ; Greco et al, 2022 ). However, it is not yet clear whether the main effect on muscle strength is given by the music characteristics ( i.e ., tempo > 120 bpm) or the affective responses consequent to listening to self-selected music.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet of Things (IoT) has revolutionized numerous industries, including music therapy [1,2], personalized music recommendation systems [3][4][5], and exercise and fitness [6][7][8][9]. Several studies have demonstrated the positive effects of music on exercise performance, mood elevation, and fatigue reduction, such as improved endurance and better adherence to exercise programs [10][11][12][13][14][15][16][17][18][19][20]. However, more studies need to explore integrating IoT with music in the context of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Studies looking at how music during the warm-up process affected athletes' short-term maximal performances discovered considerable ergogenic effects. The motivating benefits of music have been associated with improvements in self-confidence, increased physiological arousal, and enhanced motor coordination [7,18,19].…”
Section: Introductionmentioning
confidence: 99%